Deep‐water dunes on drowned isolated carbonate terraces (Mozambique Channel, south‐west Indian Ocean). Issue 4 (14th March 2019) - Miramontes, Elda; Jorry, Stephan J.; Jouet, Gwenael; Counts, John W.; Courgeon, Simon; Le Roy, Pascal; Guerin, Charline; Hernández‐Molina, F. Javier
Abstract: Subaqueous sand dunes are common bedforms on continental shelves dominated by tidal and geostrophic currents. However, much less is known about sand dunes in deep‐marine settings that are affected by strong bottom currents. In this study, dune fields were identified on drowned isolated carbonate platforms in the Mozambique Channel (south‐west Indian Ocean). The acquired data include multibeam bathymetry, multi‐channel high‐resolution seismic reflection data, sea floor imagery, a sediment sample and current measurements from a moored current meter and hull‐mounted acoustic Doppler current profiler. The dunes are located at water depths ranging from 200 to 600 m on the slope terraces of a modern atoll (Bassas da India Atoll) and within small depressions formed during tectonic deformation of drowned carbonate platforms (Sakalaves Seamount and Jaguar Bank). Dunes are composed of bioclastic medium size sand, and are large to very large, with wavelengths of 40 to 350 m and heights of 0·9 to 9·0 m. Dune migration seems to be unidirectional in each dune field, suggesting a continuous import and export of bioclastic sand, with little sand being recycled. Oceanic currents are very intense in the Mozambique Channel and may be able to erode submerged carbonates, generating carbonate sand at great depths. A mooring located at 463 m water depth on the Hall Bank (30 km west of the Jaguar Bank) showed vigorous bottom currents, with mean speeds of 14 cm sec −1 and maximum speeds of 57 cm sec −1, compatible with sand dune formation. The intensity of currents is highly variable and is related to tidal processes (high‐frequency variability) and to anticyclonic eddies near the seamounts (low‐frequency variability). This study contributes to a better understanding of the formation of dunes in deep‐marine settings and provides valuable information about carbonate preservation after drowning, and the impact of bottom currents on sediment distribution and sea floor morphology.